A Physicochemical Study of Cost-Effective Liquid Desiccants for Use in an air conditioning systems (University of Khartoum Engineering Journal, 2022)
Liquid desiccant systems (LDS) have attracted attention as promising low-energy alternative cooling solutions relative to conventional systems. An integral part of the LDS dehumidification capability depends on the composition of the hygroscopic desiccants utilized. The vapour pressure of different hygroscopic salt solutions and mixtures thereof have been measured at a temperature of 298.15K using a Yamamoto configuration. The initial validation of the measurement configuration using a single salt solution has exhibited a satisfactory correlation with vapour pressures reported by previous authors at various concentrations. The performance of MgCl2 solution was found to be comparable to that of LiCl. The results have shown that MgCl2 solution with 30% w/v concentration is sufficient to maintain the equilibrium relative humidity (ERH) at 50%, the recommended value for the human comfort zone, a value close to that obtained from LiCl solution (ERH = 55%) with the same concentration. Moreover, the best performing salt solution mixtures were found to be magnesium and lithium chlorides. Considering that the cost of LiCl is 23 times higher than that of MgCl2, the potential replacement of LiCl with MgCl2 in LDS is very promising from both a performance and cost point of view. The concentrated seawater brines have also shown a very promising performance comparable with that of 50% CaCl2– 50% MgCl2 artificial mixture.